Investigation of thermal and hydrodynamic processes in the oil transformer radiator cooling system - Ільїн, Сергій Віталійович (Technology audit and production reserves, 2013)
Despite the large number of publications in the field of transformer, heat transfer and hydrodynamic processes that take place in the radiator cooling systems, lack of attention. However, for a comprehensive analysis of the entire oil circuit in the transformer, it is necessary to take into account the work of the radiator, as it was on the efficiency of removal of heat in it will depend on the oil temperature at the inlet of the transformer. To achieve these objectives, this paper describes two methods: by experimental and mathematical modeling. The obtained results are compared both ways between themselves and the calculated error, which is reciprocal to confirming the adequacy of the results obtained by both methods. This article has been further development of the concept of heat transfer and hydrodynamic processes that take place in the radiator cooling systems of power transformers. The logical result of the reported studies, is the determination of the coefficient of heat transfer from the radiator to the cooling medium as a parameter which characterizes the intensity of the heat removal from the oil in the radiator. The results can then be used not only for calculating the cooling radiator but in general the entire transformer.